2023
DOI: 10.3390/ijms24043372
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D1 Attenuation Therapeutics Promotes Resilience against Synaptotoxicity in 12-Month-Old 3xTg-AD Mouse Model of Progressive Neurodegeneration

Abstract: Abrogating synaptotoxicity in age-related neurodegenerative disorders is an extremely promising area of research with significant neurotherapeutic implications in tauopathies including Alzheimer’s disease (AD). Our studies using human clinical samples and mouse models demonstrated that aberrantly elevated phospholipase D1 (PLD1) is associated with amyloid beta (Aβ) and tau-driven synaptic dysfunction and underlying memory deficits. While knocking out the lipolytic PLD1 gene is not detrimental to survival acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…Interestingly, PLD1 physically interacts and colocalizes with amyloid precursor protein (APP) and caveolin-3 [ 49 ]. One study discovered that APP correlates with the structural pleckstrin domain of PLD1 homolog, and that the amyloid region of APP interacts with PLD, suggesting that the upregulation of PLD1 may play a role in AD associated neuronal pathology [ 50 ]. Bourne et al [ 51 ] reported that an abnormal increase in neuronal PLD1 is crucial for oligomeric amyloid formation, which can lead to synaptic dysfunction and potential memory deficits.…”
Section: Roles Of Pld In Neurodegenerative and Neuroimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PLD1 physically interacts and colocalizes with amyloid precursor protein (APP) and caveolin-3 [ 49 ]. One study discovered that APP correlates with the structural pleckstrin domain of PLD1 homolog, and that the amyloid region of APP interacts with PLD, suggesting that the upregulation of PLD1 may play a role in AD associated neuronal pathology [ 50 ]. Bourne et al [ 51 ] reported that an abnormal increase in neuronal PLD1 is crucial for oligomeric amyloid formation, which can lead to synaptic dysfunction and potential memory deficits.…”
Section: Roles Of Pld In Neurodegenerative and Neuroimmune Diseasesmentioning
confidence: 99%
“…The PLD3 level in human prefrontal cortex was found to be inversely associated with the severity of A β pathology as well as the rate of cognitive decline in 531 participants enrolled in the aging project [ 55 ]. Accumulation of A β in the brain mediates various aspects of the pathogenesis of attention deficit disorder, and A β -stimulated PLD activity correlates with lactate dehydrogenase release, an indicator of cell death, suggesting that the neurotoxic effects of amyloid are mediated by PLD [ 50 ]. PLD1/2 is also involved in APP and presenilin trafficking and it is crucial for APP metabolism and secretion [ 56 ].…”
Section: Roles Of Pld In Neurodegenerative and Neuroimmune Diseasesmentioning
confidence: 99%